2015
DOI: 10.1186/s12885-015-1479-3
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of HER2 expression in ductal breast carcinoma in situ (DCIS); a population-based cohort study

Abstract: BackgroundHER2 is a well-established prognostic and predictive factor in invasive breast cancer. The role of HER2 in ductal breast carcinoma in situ (DCIS) is debated and recent data have suggested that HER2 is mainly related to in situ recurrences. Our aim was to study HER2 as a prognostic factor in a large population based cohort of DCIS with long-term follow-up.MethodsAll 458 patients diagnosed with a primary DCIS 1986–2004 in two Swedish counties were included. Silver-enhanced in situ hybridisation (SISH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 41 publications
2
37
1
Order By: Relevance
“…The expression of high Ki67 level (>14%) in DCIS is an independent predictor of invasive recurrence, as reported in a study of Kerlikowske et al (10). This trial show that patients with ER-negative and HER2-positive DCIS expressing high levels of Ki67 (>10%) have higher risk of local DCIS recurrence than other patient groups (10). This agree to our results, because in our analysis patients affected by HER2-positive DCIS have a higher index of cell proliferation (Ki67 >14%, p = 0.003) and express lower levels of ER (p = 0.0006) and PgR (p = 0.0009) compared to HER2-negative ones.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The expression of high Ki67 level (>14%) in DCIS is an independent predictor of invasive recurrence, as reported in a study of Kerlikowske et al (10). This trial show that patients with ER-negative and HER2-positive DCIS expressing high levels of Ki67 (>10%) have higher risk of local DCIS recurrence than other patient groups (10). This agree to our results, because in our analysis patients affected by HER2-positive DCIS have a higher index of cell proliferation (Ki67 >14%, p = 0.003) and express lower levels of ER (p = 0.0006) and PgR (p = 0.0009) compared to HER2-negative ones.…”
Section: Discussionmentioning
confidence: 88%
“…The literature suggests that patients with HER2‐amplified DCIS have more frequently high nuclear grade (G3) DCIS and this aspect is related to an increased risk of relapse, but the prognostic role of HER2‐overexpression in DCIS is still not fully solved. In fact some studies suggested that HER2 plays a major role in the transition from DCIS to IDC, while others did not . The presence of comedonecrosis and calcifications within the tumor is predictive of recurrence regardless of HER2 status, as opposed to the presence of cancerization of lobules which is more frequent in HER2‐positive patients (p = 0.049).…”
Section: Discussionmentioning
confidence: 99%
“…If for IBC, the negative impact on prognosis of HER2neu overexpresion is well establised, its role is still debate in DCIS [33]. The study of Borgquist S. et al proved that its positivity is associated with lower risk of recurrent invasive BC [34]. Recently, it was demonstrated that HER2neu amplification implies a high risk for DCIS recurrence [35].…”
Section: Discussionmentioning
confidence: 99%
“…It remains completely speculative at the present time how much, if any, HER2 status would add in addition to grade on predicting the likelihood of no residual disease at surgical resection. Most studies to date have suggested an increased risk of recurrence for HER2 positive DCIS and one study a lower risk of invasive recurrence . Thus far the studies are only hypothesis generating and our work cannot further contribute to answering this specific question.…”
mentioning
confidence: 81%
“…Most studies to date have suggested an increased risk of recurrence for HER2 positive DCIS 3,4 and one study a lower risk of invasive recurrence. 5 Thus far the studies are only hypothesis generating and our work cannot further contribute to answering this specific question. We look forward to future studies addressing this issue.…”
mentioning
confidence: 99%